Mutant prevention concentration, pharmacokinetic–pharmacodynamic integration, and modeling of enrofloxacin data established in diseased buffalo calves. Issue 6 (16th March 2015) - Ramalingam, B.; Sidhu, P. K.; Kaur, G.; Venkatachalam, D.; Rampal, S.
<x xml:space="preserve">Abstract</x> The pharmacokinetic–pharmacodynamic (PK/PD) modeling of enrofloxacin data using mutant prevention concentration (MPC) of enrofloxacin was conducted in febrile buffalo calves to optimize dosage regimen and to prevent the emergence of antimicrobial resistance. The serum peak concentration (Cmax), terminal half‐life (t1/2K10), apparent volume of distribution (Vd(area)/F), and mean residence time (MRT) of enrofloxacin were 1.40 ± 0.27 μg/mL, 7.96 ± 0.86 h, 7.74 ± 1.26 L/kg, and 11.57 ± 1.01 h, respectively, following drug administration at dosage 12 mg/kg by intramuscular route. The minimum inhibitory concentration (MIC), minimum bactericidal concentration, and MPC of enrofloxacin against Pasteurella multocida were 0.055, 0.060, and 1.45 μg/mL, respectively. Modeling of ex vivo growth inhibition data to the sigmoid Emax equation provided AUC24 h/MIC values to produce effects of bacteriostatic (33 h), bactericidal (39 h), and bacterial eradication (41 h). The estimated daily dosage of enrofloxacin in febrile buffalo calves was 3.5 and 8.4 mg/kg against P. multocida/pathogens having MIC90 ≤0.125 and 0.30 μg/mL, respectively, based on the determined AUC24 h/MIC values by modeling PK/PD data. The lipopolysaccharide‐induced fever had no direct effect on the antibacterial activity of the enrofloxacin and alterations in PK of the drug, and its metabolite will be beneficial for its use to treat infectious diseases caused by sensitive pathogens in buffalo species. In addition, in vitro MPC data in conjunction with in vivo PK data indicated that clinically it would be easier to eradicate less susceptible strains of P. multocida in diseased calves.